Innovative ZrO2-supported CuPd catalysts for the selective production of hydrogen from methanol steam reforming - C. S. R. Azenha (2017)
Low temperature methanol steam reforming (MSR) is an attractive source of nearly CO-free H-2 for fuel cells application. However, there is still a lack of efficient catalysts able to operate at low temperatures (<= 220 degrees C), where MSR is equilibrium-limited. Pd-based catalysts are regarded as an alternative to conventional Cu-based catalysts for MSR, but their low MSR selectivity limit their application. This work studies the effect of Cu as MSR promoter of Pd/ZrO2 catalysts, with special emphasis on the improvement of MSR selectivity. The influence of ZrO2 structure support, monoclinic and cubic, on the MSR behavior is also studied. CuPd/ZrO2-m catalysts with enhanced activity and MSR selectivity are developed. This superior performance was attributed to a strong interaction between Pd and Cu and an enhanced dispersion of the metal phase when ZrO2 with monoclinic structure was used as support.